Altered Regulation of Striatal Neuronal N-Methyl-D-Aspartate Receptor Trafficking by Palmitoylation in Huntington Disease Mouse Model - Kang, Rujun; Wang, Liang; Sanders, Shaun S.; Zuo, Kurt; Hayden, Michael R.; Raymond, Lynn A. (Frontiers in Synaptic Neuroscience, 2019)
N-methyl-D-aspartate receptors (NMDARs) play a critical role in synaptic signaling, and alterations in the synaptic/extrasynaptic NMDAR balance affect neuronal survival. Studies have shown enhanced extrasynaptic GluN2B-type NMDAR (2B-NMDAR) activity in striatal neurons in the YAC128 mouse model of Huntington disease (HD), resulting in increased cell death pathway activation contributing to striatal vulnerability to degeneration. However, the mechanism(s) of altered GluN2B trafficking remains unclear. Previous work shows that GluN2B palmitoylation on two C-terminal cysteine clusters regulates 2B-NMDAR trafficking to the surface membrane and synapses in cortical neurons. Notably, two palmitoyl acyltransferases (PATs), zDHHC17 and zDHHC13, also called huntingtin-interacting protein 14 (HIP14) and HIP14-like (HIP14L), directly interact with the huntingtin protein (Htt), and mutant Htt disrupts this interaction. Here, we investigated whetherGluN2B palmitoylation is involved in enhanced extrasynaptic surface expression of 2B-NMDARs in YAC128 striatal neurons and whether this process is regulated by HIP14 or HIP14L. We found reduced GluN2B palmitoylation in YAC128 striatum, specifically on cysteine cluster II. Consistent with that finding, the palmitoylation-deficient GluN2B Cysteine cluster II mutant exhibited enhanced, extrasynaptic surface expression in striatal neurons from wild-type mice, mimicking increased extrasynaptic 2B-NMDAR observed in YAC128 cultures. We also found that HIP14L palmitoylated GluN2B cysteine cluster II. Moreover, GluN2B palmitoylation levels were reduced in striatal tissue from HIP14L-deficient mice, and siRNA-mediated HIP14L knockdown in cultured neurons enhanced striatal neuronal GluN2B surface expression and susceptibility to NMDA toxicity. Thus, altered regulation of GluN2B palmitoylation levels by the huntingtin-associated PAT HIP14L may contribute to the cell death-signaling pathways underlying HD.